Workshop Pengembangan Perangkat Ajar Berbasis Literasi dan Numerasi dengan Pendekatan Deep Learning Menggunakan Model Berdampak di SD Kota Malaka - Ratu, Kurniayu Triastuti R. A.; Bulu, Vera Rosalina; Koro, Maxsel; Nawa, Netty E. A.; Kota, Martha Kristina; Daki, Sandrianus Wolo (Jurnal Kelimutu Pengabdian Masyarakat, 2025)
This Community Service (PkM) activity aimed to enhance teachers’ skills in developing learning devices based on literacy and numeracy using a deep learning approach through the BERDAMPAK model (Collaborate, Educate, Responsive, Dynamic, Adaptive, Constructive, Action Learning, and Consistent). The activity was conducted on May 10–12, 2025, at SD Inpres Laran, involving teachers as active participants. The implementation included interactive workshops, simulations for designing learning devices, and group discussions to facilitate a contextual understanding of literacy and numeracy concepts. The results indicated an improvement in teachers’ abilities to design lesson plans (RPP), modules, and learning media that support literacy- and numeracy-based learning. The BERDAMPAK model provided a collaborative, adaptive, and responsive learning experience that addressed teachers’ needs and enhanced their practical skills. This activity significantly contributed to improving the quality of teaching in elementary schools and encouraged teachers to continuously develop their professional competencies through pedagogical innovation. It strengthened technical skills in designing learning devices while fostering a culture of professionalism focused on creative, student-centered, and effective learning practices.